Integration of Islamic Sharia in National Legal System - M. Sulthon (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2020)
The purpose of this study is to answer the formulation of the problem of how is the objective condition of Islamic law in the politics of law in Indonesia and to find a concept to integrate Islamic Islamic law into State law. The research method is qualitative with a normative, philosophical and sociological approach. Substantially, the idea of formalizing Islamic law in Indonesia cannot be maximized without adaptation and reform to Islamic law, namely through ijtihad and maslahat. Every text of the Al-Qur’an and hadith that contains the law must contain maslahat. So that maslahat is an attempt to explore the meaning of the text of the Al-Qur’an. Maslahat is operationally manifested in the form of ijtihad theories, for example; qiyas, maslahah mursalah, istihsan, syad al-zdari’ah and urf. Likewise, maslahat affirmation of laws that are not contained in the Al-Qur’an and hadith, can be confirmative and can also be negative. The identification of maslahat as the essence of maqashid al-sharia is based on 1) the texts of the Al-Qur’an, the majority of which are in the form of amar and nahyu, (2) Illat and wisdom found in al-Quran and hadith, (3) al-Istiqra’.